2013
DOI: 10.1038/bjc.2013.367
|View full text |Cite
|
Sign up to set email alerts
|

The predictive impact of body mass index on the efficacy of extended adjuvant endocrine treatment with anastrozole in postmenopausal patients with breast cancer: an analysis of the randomised ABCSG-6a trial

Abstract: Background:We investigated whether body mass index (BMI) can be used as a predictive parameter indicating patients who benefit from extended aromatase inhibitor (AI) treatment.Methods:The ABCSG-6a trial re-randomised event-free postmenopausal hormone receptor-positive patients from the ABCSG-6 trial to receive either 3 additional years of endocrine therapy using anastrozole vs nil. In this retrospective analysis, we investigated the prognostic and predictive impact of BMI on disease outcome and safety.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…Also the influence of BMI on the extent of E2 deprivation during AI treatment needs further investigation, as it has not been given by weight‐ or body‐surface‐area–related dosing: one standard dosage for all patients. This might explain the worse survival for obese women undergoing endocrine treatment found in several studies …”
Section: Discussionmentioning
confidence: 98%
“…Also the influence of BMI on the extent of E2 deprivation during AI treatment needs further investigation, as it has not been given by weight‐ or body‐surface‐area–related dosing: one standard dosage for all patients. This might explain the worse survival for obese women undergoing endocrine treatment found in several studies …”
Section: Discussionmentioning
confidence: 98%
“…Thus, BMI potentially has an impact on the efficacy of AIs to lower estradiol serum levels. Indeed, retrospective analysis of phase III clinical trials demonstrated that overweight and obese patients have a worse disease outcome when treated with anastrozole compared with normal weight patients (Sestak et al , 2010; Pfeiler et al , 2011; Gnant et al , 2013). As this could not be shown for tamoxifen in these trials, BMI might be a predictive parameter regarding endocrine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while recurrence-free survival with anastrozole treatment was higher in comparison to tamoxifen, this benefit was lost in the obese cohort [56*]. Another study found that although three extra years of anastrozole treatment decreased normal weight patients’ risk of disease recurrence and death by half, overweight and obese patients did not benefit from this treatment [57]. Furthermore, plasma estradiol and estrone sulfate levels in obese patients remain significantly elevated in comparison to non-obese patients following letrozole treatment [58], suggesting that this reduced response rate is related to suboptimal inhibition of obesity-associated aromatase activity.…”
Section: Clinical Trials Of Cox-2 Inhibitorsmentioning
confidence: 99%